Respuesta :
If you would like to write a * b + c in simplest form, you can do this using the following steps:
a = x + 1
b = x^2 + 2x - 1
c = 2x
a * b + c = (x + 1) * (x^2 + 2x - 1) + 2x = x^3 + 2x^2 - x + x^2 + 2x - 1 + 2x = x^3 + 3x^2 + 3x - 1
The correct result would be x^3 + 3x^2 + 3x - 1.
a = x + 1
b = x^2 + 2x - 1
c = 2x
a * b + c = (x + 1) * (x^2 + 2x - 1) + 2x = x^3 + 2x^2 - x + x^2 + 2x - 1 + 2x = x^3 + 3x^2 + 3x - 1
The correct result would be x^3 + 3x^2 + 3x - 1.
This are expression that has a leading degree of 3 and above. The sum of ab and c in its simplest form is expressed as: x³ + 3x² + 3x -1
Polynomial expressions
This are expression that has a leading degree of 3 and above.
Given the following parameters
- a = x + 1
- b = x² + 2x - 1
- c = 2x
Required
- ab + c
Take the product of a and b
ab = (x+1)( x² + 2x - 1)
ab = x³ +2x² - x +x² + 2x -1
ab = x³ + 3x² + x -1
Take the sum of ab and c
ab + c = x³ + 3x² + x -1 + 2x
ab +c = x³ + 3x² + 3x -1
Hence the sum of ab and c in its simplest form is expressed as: x³ + 3x² + 3x -1
Learn more on polynomial here: https://brainly.com/question/2833285
#SPJ5